Fermented Kasgot and SP 36 Fertilizer as Inputs for Purple Corn Cultivation in Ultisol Soil - Hardi Rahmat Raharjo; Supartoto Supartoto; Okti Herliana (Jurnal Ilmu Pertanian Indonesia)
The purpose of this research was to determine the effect of fermentation kasgot and SP-36 fertilizer on purple corn in Ultisol soil. The research was carried out in the Screenhouse Food and Horticulture Corps Seed Agency, Bojong Village, Kembaran District, Banyumas Regency, from February to July 2022. The experiment used Randomized Block Design (RBD) with 2 treatments and 3 replications. The treatments were fermentation kasgot fertilizer with 3 levells, namely kasgot without fermentation, kasgot fermented with EM4, and kasgot fermented with Trichoderma sp.; and the second treatments were dose of SP-36 fertilizer with 3 levells, namely 50 kg/ha, 75 kg/ha, 100 kg/ha. The result showed that fermentation kasgot with EM4 increased wet crop weigth to 9,03% and wet seeds weight by corncob to 27,56%, while fermented kasgot with Trichoderma sp. increased dry seeds weight by corncob to 29,13%. SP-36 fertilizer effect in corncob diameter and P uptake in plant. Dose of 50 kg/ha increased corncob diameter to 6,58% and P uptake in plant to 23,03%. There was significant interaction between fermented kasgot with EM4 and SP-36 fertilizer dose by 50 kg/ha that increased dry plant weight to 36,98%.